Performance Analysis of Cluster Based Routing Protocol for Ad hoc Networks - Khiratkar, Gangotri A; Mahajan, Swati S (International Journal of Computer Sciences and Engineering, 2014)
A Mobile Ad hoc Network (MANET) is a collection of wireless devices that can exchange information dynamically. The nodes in the network exchange information using the topology of the network. The ad-hoc network suffers from excessive traffic and maximum control overheads during route discovery. In this paper we have describe the clustering approach in ad-hoc network. The cluster based routing protocol (CBRP) divide the network in to small groups. The cluster head is elected to manage a cluster. Cluster heads in the network are responsible for information exchange. Using clustering approach flooding and overhead problems within the network can be effectively minimized.